Theory about traumatic brain injury effects. Part III. Conceptual approaches to treatment of traumatic brain injury effects - Leonid B. Likhterman; Aleksandr D. Kravchuk; Vladimir A. Okhlopkov (LLC "MEDIAFORMAT", 2021)
Conceptual or systemic approaches to treatment of the traumatic brain injury effects developed by the authors have been reported, which are based on studying the pathogenesis and sanogenesis of the disorder. The use of those has markedly improved the results of treating the skull and brain abnormalities, caused by traumatic brain injury, due the to increased use of the minimally invasive and reconstructive surgery.